Java EE 8 and Angular : a practical guide to building modern single-page applications with Angular and Java EE - Padmanabhan, Prashant (Packt Publishing, 2018)
Learn how to build high-performing enterprise applications using Java EE powered by Angular at the frontend About This Book Leverage Java EE 8 features to build robust back end for your enterprise applications Use Angular to build a single page frontend and combine it with the Java EE backend Practical guide filled with ample real-world examples Who This Book Is For This book is for Java EE developers who would like to build modern enterprise web applications using Angular. No prior knowledge of Angular is expected. What You Will Learn Write CDI-based code in Java EE 8 applications Build an understanding of Microservices and what they mean in Java EE context Use Docker to build and run a microservice application Use configuration options to work effectively with JSON documents Understand asynchronous task handling and writing REST API clients Explore the fundamentals of TypeScript, which sets the foundation for working on Angular projects Use Angular CLI to add and manage new features Use JSON Web tokens to secure Angular applications against malicious attacks In Detail The demand for modern and high performing web enterprise applications is growing rapidly. No more is a basic HTML front-end enough to meet customer demands. This book will be your one stop guide to build outstanding enterprise web applications with Java EE and Angular. It will teach you how to harness the power of Java EE to build sturdy back ends while applying Angular on the front end. Your journey to building excellent web enterprise applications starts here! The book starts with a brief introduction to the fundamentals of Java EE and all the new APIs offered in the latest release. Armed with the knowledge of Java EE 8, you will go over what it's like to build an end to end application, configure database connection for JPA, and build scalable microservice using RESTful APIs running in docker containers. Taking advantage of Payara Micro capabilities, you will build an Issue Management System, which will have various features exposed as services using Java EE backend. With a detailed coverage of Angular fundamentals, the book will expand the Issue Management System by building a modern single page application frontend. Moving forward you will learn to fit both the pieces together i.e. the frontend Angular application with the backend java EE microservices. As each unit in a microservice promotes high cohesion, you will learn different ways in which independent units can be te ...